Gestión curricular integradora, para el aseguramiento del aprendizaje: una apuesta por la calidad de la educación superior (2024)
In the field of higher education, the quality and relevance of curricular proposals articulated to the real needs of the contexts are essential to ensure comprehensive training and prepare students for the challenges of today's professional world. In this sense, the purpose of this doctoral thesis is to generate a model of integrated curriculum management, which from systemic and transversal relations contributes to the assurance of learning and the improvement of higher quality, through problematising axes connected to the reality of the contexts. The methodological route of the study was upported by a critical rationalist approach, a mixed paradigm, with an analytical-explanatory-propositive scope. The techniques of documentary analysis of documents, surveys, semi-structured interviews with experts in curriculum issues and validation workshops with key actors in curriculum management were applied. The units of analysis and informants were key educational actors in curriculum management in undergraduate and postgraduate academic programmes. The results of the research indicate that the assurance of learning and the improvement of the quality of educational processes in higher education suggest models of curriculum management that, through the principle of transversality of problematising axes, dynamise the educational experience and enhance the development of capacities. Finally, the theoretical, methodological and operational guidelines of the Integrated Curricular Management Model are proposed for the articulation of the macro, meso- and micro-curricular levels. Furthermore, the validation of the model highlights a clear, theoretically developed and operable route to contribute to the assurance of student learning and the improvement of higher education.